PyTorch Genesis - A Framework for Neuroevolution Neurevolution Using Genetic Programming and Backpropagation - Santos, Frederico José Jácome de Brito (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science